Utilization of Areca Nut Leaf Sheath Fibers for the Extraction of Cellulose Whiskers. Issue 9 (2nd September 2021) - Elanthikkal, Silviya; Francis, Tania; Akhtar, Sultan
ABSTRACT: In this study, cellulose whiskers were extracted from an agricultural plant waste, Areca Nut Leaf Sheath, by employing a sulfuric acid hydrolysis method. The effect of hydrolysis time and temperature on the morphology, crystallinity, and degree of polymerization of the resultant cellulose particles was studied. Highly crystalline cellulose whiskers with an aspect ratio around 20 were obtained under moderate conditions of hydrolysis by maintaining the temperature at 45°C and hydrolysis time of 180 min. However, on increasing the temperature and time of hydrolysis, surface flattening of fibers was observed and aspect ratio was decreased. Isolated cellulose whiskers were found to contain traces of biosilica. Graphical Abstract: uf0001